2016
DOI: 10.1016/j.ultrasmedbio.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of a Single-Element Ultrasound Viscoelastography System for Point-of-Care Edema Quantification

Abstract: Management of fluid overload in patients with end stage renal disease represents a unique challenge where clinical practice still lacks accurate and objective measurement methods. Currently, peripheral edema is subjectively assessed by palpation of the patient's extremities, ostensibly a qualitative indication of tissue viscoelastic properties. New robust quantitative estimates of tissue fluid content would allow clinicians to better guide treatment, minimizing reactive treatment decision making. Ultrasound vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A limited number of novel developments strive to leverage ultrasound to quantify observations of edema and to measure the depth of pitting edema [ 173 175 ]. In a clinical study, the relationship between surface imprint depth, circumferential measurement, and tissue thickness revealed that depth of surface imprints correlate with subcutaneous tissue thickness by a coefficient of 0.736 [ 174 ].…”
Section: Non-invasive Vca Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of novel developments strive to leverage ultrasound to quantify observations of edema and to measure the depth of pitting edema [ 173 175 ]. In a clinical study, the relationship between surface imprint depth, circumferential measurement, and tissue thickness revealed that depth of surface imprints correlate with subcutaneous tissue thickness by a coefficient of 0.736 [ 174 ].…”
Section: Non-invasive Vca Evaluation Methodsmentioning
confidence: 99%
“…In a clinical study, the relationship between surface imprint depth, circumferential measurement, and tissue thickness revealed that depth of surface imprints correlate with subcutaneous tissue thickness by a coefficient of 0.736 [ 174 ]. In a similar manner, Pitre and colleagues considered the viscoelasticity of tissue as a measure of edema status and simplified hardware by designing a single-element ultrasound transducer [ 175 ]. Graphing tissue viscoelasticity across simulated edema conditions indicated depth dependency, therefore providing enhanced quantification of superficial edema.…”
Section: Non-invasive Vca Evaluation Methodsmentioning
confidence: 99%
“…(14) Water immersion volumetry has been considered the criterion standard, but even this has been called into question by techniques such as optoelectronic volumetry. (15) Bioimpedance spectroscopy(16) (BIS) or ultrasound viscoelastography (17) offer novel techniques, but require sophisticated technology and presumably high cost. There is one important proviso regarding these techniques: none except for direct edema testers is able to determine whether a patient actually has edema: "volumetry does not quantify edema but rather the short-term variations that re ect changes in edema".…”
Section: Introductionmentioning
confidence: 99%
“…However, as the properties of biological tissue were progressively understood, a variety of theoretical frameworks were developed and integrated with earlier elastography techniques. In recent years, although the name of elastography remains largely unchanged (some studies have adopted the term "viscoelastography" [11,12]), it has become more common that quantitative values of various moduli, as we will discuss in detail in later sections, include information of material viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%